A validation study of combined resection and ablation therapy for multiple hepatocellular carcinoma. Issue 2 (February 2022) - Tada, T.; Kumada, T.; Toyoda, H.; Nakamura, S.; Endo, Y.; Kaneoka, Y.; Hiraoka, A.; Joko, K.; Hirooka, M.; Hiasa, Y.
Abstract : AIM: To validate the utility of hepatic resection combined with complementary radiofrequency ablation (RFA) compared with resection alone for patients with multiple hepatocellular carcinoma (HCC), and to compare these results with those of a previous report. MATERIALS AND METHODS: A total of 78 HCC patients with multiple (≤5) tumours who were initially treated with hepatic resection only (Resection group) or with combined hepatic resection and RFA (Combination group) were included. Overall and disease-free survival were analysed. RESULTS: There were 21 women and 57 men with a median age of 72.5 (64.3–76.8) years. Fifty-three patients were treated with resection alone and 25 received combination therapy. The 3-, 5-, and 7-year cumulative overall survival rates were 81.2%, 68.2%, and 57.1%, respectively, in the Resection group, and 81.3%, 59.6%, and 42.4%%, respectively, in the Combination group (hazard ratio [HR], 1.462; 95% confidence interval [CI], 0.682–3.136; p= 0.329). The 1-, 3-, and 5-year cumulative disease-free survival rates were 61.4%, 45.7%, and 39.8%, respectively, in the Resection group, and 53.1%, 18.6%, and 0%, respectively, in the Combination group (HR, 2.080; 95% CI, 1.157–3.737; p= 0.014). The overall survival rate was not significantly different between the Resection and Combination groups in patients within the up-to-seven HCC criteria ( n= 56; HR, 2.101; 95% CI, 0.805–5.486; p= 0.130) or those beyond these criteria ( n= 22; HR, 0.804; 95% CI, 0.197–3.286; p= 0.761). CONCLUSIONS: The combination of hepatic resection and RFA therapy may be an effective strategy for HCC patients with multiple tumours. Highlights: To validate the utility of hepatic resection combined with RFA for multiple HCC. The overall survival was not different between the resection and combination therapy. The combination of resection and RFA may be an effective strategy for multiple HCC.